2019
DOI: 10.3390/ijerph16152667
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors Associated with Quality of Life in Young Men Who Have Sex with Men Living with HIV/AIDS in Zhejiang, China

Abstract: Objectives: To explore the quality of life (QOL) status and related factors in young human immunodeficiency virus (HIV)-infected men who have sex with men (MSM) aged 16 to 24 years in Zhejiang province. Methods: A cross-sectional study was conducted in 22 counties of Zhejiang province, and 395 subjects took part in our research. A t-test, one-way Analysis of variance (ANOVA), and multivariate stepwise linear regression analysis were used to investigate the factors associated with QOL in young HIV-infected MSM.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 43 publications
0
11
1
1
Order By: Relevance
“…The results showed there was a significant positive relationship between QoL domain scores and intensities of recovery of HIV-infected patients. Studies conducted in South Africa [52] and China [53] revealed a similar finding where a better QoL score significantly associated with a higher CD4 count.…”
Section: Discussionmentioning
confidence: 54%
“…The results showed there was a significant positive relationship between QoL domain scores and intensities of recovery of HIV-infected patients. Studies conducted in South Africa [52] and China [53] revealed a similar finding where a better QoL score significantly associated with a higher CD4 count.…”
Section: Discussionmentioning
confidence: 54%
“…The US study observed signi cantly lower levels of depression and fewer conduct problems in adolescents whose parents were infected with HIV revealed that with more social support (26). The Chinese study revealed a better QOL among young men who have sex with men living with HIV who had greater social support (27). This domain is believed to be an important component which affected overall QOL.…”
Section: Discussionmentioning
confidence: 97%
“…Higher mortality among older males may be attributed to their late diagnosis, comorbidities, and poor immunological responses to ART [ 28 , 29 ]. Educational level was negatively associated with AIDS-related mortality, probably because individuals with high education were more likely to adopt protective measures than others [ 30 , 31 ]. Lower AIDS-related mortality risk was observed among married patients, which related with fewer sexual partners [ 32 ].…”
Section: Discussionmentioning
confidence: 99%